Interactions between sympatric invasive European fire ants (Myrmica rubra) and blacklegged ticks (Ixodes scapularis). - Lucy D Guarnieri (Public Library of Science (PLoS), 2021)
The blacklegged tick (Ixodes scapularis) and the invasive European fire ant (Myrmica rubra) are both expanding throughout their sympatric range in coastal New England. Ixodes scapularis is the primary vector of the bacterium Borrelia burgdorferi, which is the causative agent of Lyme disease, and Mount Desert Island, Maine, home to Acadia National Park, currently is affected by a high Lyme disease burden. Ticks have many natural predators, including ants, although no previous studies have investigated interactions between these two species. To test the hypothesis that the presence of M. rubra alters I. scapularis abundance, we collected ticks by drag-sampling at eight ant-infested sites and eight uninfested control sites in Acadia National Park. We found that nymph density was significantly higher at ant-infested sites, while larval density was significantly higher at control sites. In addition, we conducted a laboratory bioassay to measure M. rubra aggression against I. scapularis larvae, nymphs, and adults and Dermacentor variabilis adults, and found that ant aggression was significantly higher against D. variabilis adults than I. scapularis adults. Our findings support the hypothesis that M. rubra has divergent effects across I. scapularis life stages, and we discuss possible ecological mechanisms, including optimal microclimate and predation, that could promote density of nymphs while inhibiting density of larvae.